Aerospace series. Sleeving, heat-shrinkable, for binding, insulation and identification. Polytetrafluoroethylene (PTFE). Operating temperatures. 65 °C to 260 °C. Product standard Part 107, (7th October 2019) - British Standards Institution,
No abstract available